If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xt + ys = 250 Reorder the terms: sy + tx = 250 Solving sy + tx = 250 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1tx' to each side of the equation. sy + tx + -1tx = 250 + -1tx Combine like terms: tx + -1tx = 0 sy + 0 = 250 + -1tx sy = 250 + -1tx Divide each side by 'y'. s = 250y-1 + -1txy-1 Simplifying s = 250y-1 + -1txy-1 Reorder the terms: s = -1txy-1 + 250y-1
| X+5(3x-9)+7=0 | | 2a+3(1+3a)=36 | | 3(-3+3n)-1=-37 | | 4x+x^2-1020=0 | | 2tan^2x-5tanx-1=0 | | (3x+5)(x^2+4x-5)=0 | | 564b-46+44=21994 | | 2(3u-17)=16 | | (2a+4)+5(a-4)= | | 4a+2=A | | x^2+6x+6=8 | | 5ln(x)-2=0 | | 12(3x-8)=38 | | 2(3x-18)=38 | | x*(x-21)=-108 | | x^4+y^4=12xy | | 5k=30k+100 | | 7(2x-5)-4(x-20)=x-5 | | 5+30x=15+11 | | Y=20+.2x | | 3x=-9y+33 | | y=mx+c(c) | | 7s+6=8s+15 | | 7p-5p=20 | | 4j=7j+6 | | Y=4x^2-3x^3 | | 6-(3y-8)=5-4y | | -z=-4z+6 | | 6.4(x-4)=19.5 | | -w=-5w+16 | | 3z/4=2z/3-5 | | -10x=75 |